Umblical myiasis in a newborn: a case report - Jauhari, Shalabh; Nautiyal, Sulekha (International Journal Of Community Medicine And Public Health, 2017)
Myiasis is defined as the infestation of live vertebrates (humans and/or animals) with dipterous larvae. We present a case of rare but not unknown type of myiasis, presented by an 11 days old neonate. The larvae were characterised microscopically. Poor sanitation is probably the most important risk factor for human myiasis. Umblical myiasis though a rare presentation due to improved health conditions and health education still remains an entity to be looked for in case of newborn belonging to low socio economic status parents and even in orphanages.